A note on quasi-hemi slant submanifolds of nearly trans-Sasakian manifolds - Shamsur Rahman; Amit Kumar Rai (Journal of Hyperstructures, 2023)
Here our main objective is to introduce the notion of quasi hemi-slant submanifolds as a generalized case of slant sub-manifolds, semi-slant submanifolds and hemi-slant submanifolds of contact metric manifolds. We mainly focus on quasi hemi-slant sub-manifold of nearly trans-Sasakian manifold. During this manner, we tend to study and investigate integrability of distributions which are concerned in the definition of quasi hemi-slant submanifold of nearly trans-Sasakian manifold. Moreover, we tend to get necessary and sufficient conditions for quasi hemi-slant submanifold of nearly trans-Sasakian manifold to be totally geodesic for such manifolds.